1997
DOI: 10.1029/97gl01789
|View full text |Cite
|
Sign up to set email alerts
|

Darwin sea level pressure, 1876–1996: Evidence for climate change?

Abstract: Abstract. It has been argued that there was a period of prolonged ENSO conditions between 1990-95 so anomalous that it is "highly unlikely" to be due to "natural decadal-timescale

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 10 publications
0
40
1
Order By: Relevance
“…For example, Trenberth and Hoar (1996) pointed out there has been a tendency toward more frequent El Niñ o events and fewer La Niñ a events since the late 1970s and that the prolonged 1990-95 El Niñ o event was highly unusual, which may serve as evidence of the effect of anthropogenically forced global warming and related climate change. However, this conclusion was challenged by two subsequent studies (Harrison and Larkin 1997;Rajagopalan et al 1997), which suggested that the 1990-95 El Niñ o event might have been part of the natural variability. However, using the definition of El Niñ o proposed by Trenberth (1997), Trenberth and Hoar (1997) argued that the (then) newly underway El Niñ o event of 1997 further confirmed that the tendency for more El Niñ o and fewer La Niñ a events since the late 1970s is very unlikely to be accounted for solely by natural variability.…”
Section: Introductionmentioning
confidence: 81%
“…For example, Trenberth and Hoar (1996) pointed out there has been a tendency toward more frequent El Niñ o events and fewer La Niñ a events since the late 1970s and that the prolonged 1990-95 El Niñ o event was highly unusual, which may serve as evidence of the effect of anthropogenically forced global warming and related climate change. However, this conclusion was challenged by two subsequent studies (Harrison and Larkin 1997;Rajagopalan et al 1997), which suggested that the 1990-95 El Niñ o event might have been part of the natural variability. However, using the definition of El Niñ o proposed by Trenberth (1997), Trenberth and Hoar (1997) argued that the (then) newly underway El Niñ o event of 1997 further confirmed that the tendency for more El Niñ o and fewer La Niñ a events since the late 1970s is very unlikely to be accounted for solely by natural variability.…”
Section: Introductionmentioning
confidence: 81%
“…In comparison, the numbers of strong La Nin Äa and El Nin Äo events were equal during the period 1876±1976. The recent shift toward the predominance of El Nin Äo-type conditions is re¯ected in a decrease in the mean value of the Southern Oscillation Index (Trenberth, 1990;Trenberth & Hurrell, 1994;Trenberth & Hoar, 1996Solow, 1995;Harrison & Larkin, 1997;Rajagopalan, Hall & Cane, 1997). The downward shift in the mean may not simply be a re¯ection of an increase in the frequency and/or magnitude of low-phase (El Nin Äo) events, but may re¯ect a change in the background climate state (Graham, 1994;Kleeman, Colman, Smith & Power, 1996).…”
Section: Change In the Background Climate Statementioning
confidence: 91%
“…For example, this simple analysis does not place any additional weight on high wind events and on wind duration. In addition, the length of our record does not permit rigorous determination of effective degrees of freedom (e.g., Leith et al, 1973;Harrison and Larkin, 1997) to filter out other cyclic and auto-correlated variations, such as diurnal influences on wind speeds and seasonal changes in radiation. Despite these limitations, we think that our interpretation of the association of watercolumn data and lagged wind vectors may be instructive for future research efforts in the Bering Strait.…”
Section: Resultsmentioning
confidence: 99%